The Limits of Model-Based Regulation - Markus Behn; Rainer Haselmann; Vikrant Vig (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
Using loan-level data from Germany, we investigate how the introduction of model-based capital regulation affected banks' ability to absorb shocks. The objective of this regulation was to enhance financial stability by making capital requirements responsive to asset risk. Our evidence suggests that banks 'optimized' model-based regulation to lower their capital requirements. Banks systematically underreported risk, with under reporting being more pronounced for banks with higher gains from it. Moreover, large banks benefitted from the regulation at the expense of smaller banks. Overall, our results suggest that sophisticated rules may have undesired effects if strategic misbehavior is difficult to detect.
urn:nbn:de:hebis:30:3-616608
Keywords: G01; G21; G28; 330; capital regulation; internal ratings; complexity of regulation; Basel regulation